A complicated case of an intracranial epidermoid cyst - Abdelkader Dib; Johny Salem; Marwan Haddad; Omar Awar; Mirna Fares (European Journal of Case Reports in Internal Medicine)
Intracranial vasospasm and ischaemic cerebrovascular accident (CVA) following surgical removal of intracranial tumours are rare. To our knowledge, vasospasm has been reported in only two cases following surgery, with one occurring two weeks post-surgery and the other after four days. However, ischaemic CVA following surgery has not been previously reported. We present a case in which vasospasm resulted in cerebral infarction immediately postoperatively. MRI and serial magnetic resonance angiography (MRA) revealed no flow in the internal carotid artery and middle cerebral artery, with ultrasound showing multiple thrombi in the internal carotid artery and stenotic features in the left middle cerebral artery.